Réponses

2014-04-03T14:20:11+02:00
A) (x+1)²-36 = (x+1)²-(6)²
 
Cette expression est de la forme a²-b² avec a = x +1 et b = 6 
Rappel : a
²-b² = (a+b)(a-b)

  (x+1)²-36 = (x+1+6)(x+1-6) 
                 = (x+7)(x-5)


b) 25-(2x+3)² = (5)² - (2x+3)²

Cette expression est de la forme a²-b² avec a = 5 et b = 2x+3

25-(2x+3)² = (5+2x+3)(5-2x-3) = (2x+8)(-2x+2)

c) (8x-4)²-9x² = (8x-4)²-(3x)²

Cette expression est de la forme a²-b² avec a = 8x-4 et b = 3x

(8x-4)
²-9x² = (8x-4+3x)(8x-4-3x)
                 = (11x-4)(5x-4)  

d) 4x²-(x-5)² = (2x)²-(x-5)²

Cette expression est de la forme a²-b² avec a = 2x et b = x-5

4x²-(x-5)² = (2x+x-5)(2x-x+5) 
                = (3x-5)(x+5)